INFLUENCING SYMPTOMS OF URINARY STRESS INCONTINENCE THROUGH PHYSIOTHERAPY - Petya Parashkevova; Radoslava Deleva (Peytchinski Publishing, 2023)
Purpose: Urinary incontinence leads to adverse life changes and psychological stress among patients. The purpose of this report is to follow the effect of implementing a specific exercise program in women with urinary stress incontinence. Material: The study included 30 women who completed a specialized kinesitherapy program over 16 weeks. It included exercises to strengthen the back, abdominal and gluteal muscles, Kegel exercises and balance exercises. Results: A one-hour Pad test was used to monitor the effect of applied kinesitherapy. Results are reported as means with standard deviations with 95% confidence intervals. Conclusions: The obtained results show that specialized exercises have a beneficial effect on the tone of the pelvic floor muscles and reduce the symptoms of urinary stress incontinence.